METHODOLOGY OF THE FORMATION OF GENERAL VOCATIONAL TRAINING IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS ON THE BASIS OF COMPETENCY APPROACH - Najmiddinova Yokutkhon Rukhiddinovna , Inamov Dilmirza Dadamirzaevich , Davronova Mukhayo Usubjanova , Inamiddinova Dilorom Kiramidinovna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article describes the content of the formation of general vocational training in students of higher education on the basis of a competency-based approach, the analysis of the literature in this field, the pedagogical conditions for the formation of general vocational training. Besides, it reveals the methodological system of the formation of general vocational training on the basis of a competency-based approach to the students of higher educational institutions, the content of pedagogical design of the process of individual industrial education aimed at the formation of general vocational training on the basis of a competency-based approach.